2020
DOI: 10.1021/acs.jpcc.0c09317
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Photoluminescence and Carrier Characteristics of Excited FAPbBr3 Nanocrystals with Pressure

Abstract: Halide perovskite nanocrystals (NCs) have great potential in the field of optoelectronics, owing to their excellent photophysical characteristics. Herein, the photoluminescence (PL) characteristics (involving the PL quantum yield (QY) and radiative lifetime) and carrier dynamics of FAPbBr 3 NCs have been further investigated by applying the pressure. Pressure-dependent steady spectral data confirm that FAPbBr 3 NCs pass through a cubic Pm3̅ m, a cubic supercell Im3̅ , and an orthorhombic Pnma in turn. The deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
2
10
1
Order By: Relevance
“…Other studies of bandgap changes in lead halide perovskites have been reported, for example in CsPbBr 3 where the bandgap energy increased at very high pressures >1 GPa due to lattice amorphization [25,26]. Reports of high pressure studies of FAPbBr 3 nanoparticle showed phase transitions and changes in bandgap energies at pressures in the range 1-4 GPa [27][28][29]. However these effects were observed at pressures significantly greater than those used in our study.…”
Section: Photoluminescence Studiescontrasting
confidence: 58%
“…Other studies of bandgap changes in lead halide perovskites have been reported, for example in CsPbBr 3 where the bandgap energy increased at very high pressures >1 GPa due to lattice amorphization [25,26]. Reports of high pressure studies of FAPbBr 3 nanoparticle showed phase transitions and changes in bandgap energies at pressures in the range 1-4 GPa [27][28][29]. However these effects were observed at pressures significantly greater than those used in our study.…”
Section: Photoluminescence Studiescontrasting
confidence: 58%
“…In addition, the amount of FA + with respect to Pb 2+ present in the reaction system also remained crucial. From literature reports on cube-shaped FAPbBr 3 , it is revealed that in almost all cases (see Table S1) [FA + ] was taken to be higher than or equal to [Pb 2+ ]. ,, ,,, In contrast, for dodecahedrons, [Pb 2+ ] was maintained higher than [FA + ] ([Pb 2+ ]/[FA + ] > 1) in the reaction medium. Minimum [FA + ] in the reaction medium (in comparison to [Pb 2+ ]) was targeted here for allowing ligands to bind surface A-sites and control the facet architecture of these nanocrystals.…”
mentioning
confidence: 99%
“…Therefore, their steady absorption and PL spectral feature are much similar, owing to the disappearance of the quantum confinement effect and the same chemical composition. Based on the integrating sphere, their PL quantum yields (PLQYs) can be probed and are estimated to be about 75.7% for CsPbBr 3 HNCs and 68.1% for CsPbBr 3 CNCs, which is much similar to those in a previous report . Apparently, CsPbBr 3 HNCs possess a high PLQY in comparison with that of CsPbBr 3 CNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Applying pressure is another method to adjust the structure of semiconductor materials besides changing the temperature. , A fundamental understanding of the effects of pressure on the microscopic photophysical dynamics that underpin the optimized performance of perovskite nanomaterials is indispensable to unscrambling the structure–property relationship. Based on the DAC, the physical properties of halide perovskite materials involving MAPbI 3 , , FAPbI 3 , MAPbBr 3 , , CsPbBr 3 , , , CsPbI 3 , and CsPbCl 3 can be easily regulated by pressure, such as band-gap adjustment, , prolongation of carrier lifetime, and piezochromism. However, there are few studies on the pressure of perovskite nanocrystals with special morphologies.…”
Section: Resultsmentioning
confidence: 99%